Phenotypic characterization and epidemiology of extended-spectrum β-lactamase-producing Enterobacteriaceae strains from urinary tract infections in Garoua, Cameroon - Karyom Djim-; Karyom Djim-; Karyom Djim-; Brunel W. Mbiakop; Brunel W. Mbiakop; Leila A. Oumar; Hermann L. Munshili Njifon; Cedric Tchinda Fossi; Elisee L. Embolo Enyegue; Mohamed M. Mouiche Mouliom; Siméon P. Fodouop Chegaing; Louis Deweerdt; et al. (Frontiers Media S.A., 2023)
Background and objectivesThe emergence of extended-spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-E) is causing increased morbidity and mortality around the world as a result of therapeutic failures. ESBL-E are priority pathogens due to their multidrug resistance (MDR). In Northern Cameroon, ESBL-producing bacteria, particularly in urinary tract infections (UTIs), are being increasingly isolated. This study aimed to retrospectively determine the prevalence of multi-drug resistant ESBL strains isolated from UTIs in Northern Cameroon and to evaluate the effectiveness of the ATB UR Gallery of BioMérieux in diagnosing ESBL-E in clinical settings.MethodsStandard microbiology protocols and statistical tools were utilized to identify ESBL-producing bacteria and characterize their phenotypic susceptibility and resistance profiles in the study population.ResultsOut of the 144 enterobacteria isolates successfully cultured, 59 (41%) were identified as MDR strains. The ATB UR EU gallery identified 33 (23%) multi-drug resistant ESBL-producing strains, while the double synergy test identified 35 strains without disc reconciliation and 38 strains after reconciliation. The most prevalent ESBL-E isolate was Escherichia coli, accounting for 77.1% of the isolates, followed by Klebsiella pneumoniae (20%) and Enterobacter aerogenes (2.9%). Additionally, the study revealed the emergence of Imipenem resistance (5.7%), a critical last-resort antibiotic. However, all ESBL strains were sensitive to Fosfomycin (FSF/FOS), demonstrating its potential as an effective therapeutic option. Moreover, 37% of the ESBL producers exhibited co-resistance to over 20 different antibiotics.ConclusionThis study provides valuable insights into the prevalence and susceptibility patterns of ESBL-E associated with UTIs in Northern Cameroon. These insights emphasizes the importance of implementing appropriate treatment guidelines and antimicrobial stewardship measures to mitigate the spread and impact of MDR ESBL-producing strains on public health.